An analysis of water quality discharging into the Berg River at Paarl, Western Cape - Mgese, Sivile (Department of Environmental and Geographical Science, 2015)
In densely settled urban and peri-urban areas of South Africa, stormwater infrastructure is frequently being used as a conduit for the daily discharge of effluents resulting in the deterioration of rivers and other receiving water bodies. This study investigates the pollution load from urban localities entering the Berg River at Paarl, and in particular, seeks to determine whether or not there is a difference in the pollution load immediately after periods of wet and dry weather conditions.